Product placement within national soap operas - Pereira, Francisco José Costa (2021)
The aim of this study is to evaluate the current status of product placement within fictional programs in Portugal, especially in soap operas, and to fully understand the commercial and social scope of this phenomenon. In order to carry out this study we selected the soap operas with largest audiences of the private TV channels operating in Portugal, comparing soap operas for an adult audience with those for a young audience. In all the soap operas we found diverse categories for adult and young audiences. Although with some differences, the category of products “clothing” is the main one for both audiences, and in our opinion this is due to its importance for the self image of each of these groups.